2018
DOI: 10.1021/acs.est.7b05152
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Methylmercury Production Revisited

Abstract: Laboratory measurements of the biologically mediated methylation of mercury (Hg) to the neurotoxin monomethylmercury (MMHg) often exhibit kinetics that are inconsistent with first-order kinetic models. Using time-resolved measurements of filter passing Hg and MMHg during methylation/demethylation assays, a multisite kinetic sorption model, and reanalyses of previous assays, we show that competing kinetic sorption reactions can lead to time-varying availability and apparent non-first-order kinetics in Hg methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 37 publications
0
20
1
Order By: Relevance
“…Recent studies suggested a transient availability rate potentials calculation, a modification of the original Hg methylation kinetic model from H. Hintelmann et al ( 43 ) through the determination and addition of sorption reaction kinetics, leading to k m 15 times higher than the full availability rate potentials ( 29 , 44 ). However, the remoteness of our sites and field laboratory has prevented the determination of such additional sorption constants to fit the equations.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies suggested a transient availability rate potentials calculation, a modification of the original Hg methylation kinetic model from H. Hintelmann et al ( 43 ) through the determination and addition of sorption reaction kinetics, leading to k m 15 times higher than the full availability rate potentials ( 29 , 44 ). However, the remoteness of our sites and field laboratory has prevented the determination of such additional sorption constants to fit the equations.…”
Section: Resultsmentioning
confidence: 99%
“…Hg and MeHg in contact with periphyton are subject to other reactions in addition to methylation and demethylation, including sorption, desorption, and, in the case of Hg II , reduction to Hg 0 and its reoxidation. These ancillary reactions were measured, and a novel model was created-the transient availability model (TAM)-to more accurately describe the periphyton methylation-demethylation results (Olsen et al 2018). Consistent with lab incubations data of field-derived samples from EFPC, the TAM reproduced concentration versus time behavior that had previously been thought to be anomalous.…”
Section: Field-informed Laboratory Experiments Identify a Dominant So...mentioning
confidence: 88%
“…Methylation and demethylation rate potentials were calculated using the transient availability kinetic model described by Olsen et al (). The transient availability model incorporates kinetic expressions for multisite sorption of Hg and MMHg and Hg reduction to Hg 0 with methylation/demethylation kinetics to account for these competing processes when estimating methylation/demethylation potentials (Olsen et al ). Transient availability kinetics are described by Equations 1 and 2, d[Hg]dt=0.25emkm[Hg]+kd[MMHg]k1[Hg]+k2[Hgf]k3[Hg]+k4[Hgs]k5[Hg]+k6[Hg0] d[MMHg]dt=km[Hg]kd[MMHg]k7[MMHg]+k8[MMHgf]k9[MMHg]+k10[MMHgs]where k m is the methylation rate constant, k d is the demethylation rate constant, k 1 is the Hg fast site sorption rate constant, k 2 is the Hg fast site desorption rate constant, k 3 is the Hg slow site adsorption rate constant, k 4 is the Hg slow site desorption rate constant, k 5 is the rate constant for the conversion of Hg to Hg 0 , k 6 is the rate constant for the conversion of Hg 0 to Hg, Hg f is the amount of Hg sorbed to fast sorption sites, Hg s is the amount of Hg sorbed to slow sorption sites, k 7 is the MMHg fast site adsorption rate constant, k 8 is the MMHg fast desorption rate constant, k 9 is the MMHg slow adsorption rate constant, k 10 is the MMHg slow desorption rate constant, MMHg f is the amount of MMHg sorbed to fast sites, and MMHg s is the amount of MMHg sorbed to slow sites.…”
Section: Methodsmentioning
confidence: 99%
“…However, the estimates for MMHg production from the Olsen et al (2016) study were generated with single-time point first-order kinetic models that assumed full bioavailability of Hg and MMHg. Recently, a new model for MMHg production kinetics has been developed, which accounts for the transient availability of Hg and MMHg for methylation and degradation reactions over time (Olsen et al 2018). The transient availability kinetic model provided estimates for periphyton MMHg generation and degradation rate potentials that were 25 times and 5 times higher, respectively, than full availability, single-time point estimates (Olsen et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation